DUCTILE ANALYSIS ON FRAME-SHEAR WALL STRUCTURAL SYSTEM USING SECANT STIFFNESS METHOD - PERMANA (NIM 25006017), EDO
Inelastic behavior from elements that forms a structure that subjects to earthquake is very essential in analyzing and designing an earthquake resistant structure. Two static nonlinear methods has been developed, Capacity Spectrum Method (CSM, ATC 1996) and Direct Displacement-Based Design Method (DDBD, Priestley 2000). Although these methods can estimate inelastic behavior of a structure that subjects to earthquake, they have several disadvantages in theirs applications. Capacity Spectrum Method can only be applied if the analytical model of the structure has been established beforehand, while Direct Displacement-Based Design Method has difficulties in determining the inelastic behavior of each elements of the structure because it requires a simplification from a complex model (MDOF) to a simpler model (SDOF). A new seismic design method by using linear approach is applied in analyzing ductility of structures that subject to earthquake load. This method uses linear analysis by using secant stiffness so that its application in numerical analysis is very convenient and stable. Unlike other nonlinear methods which need pushover analysis or concrete reinforcement design, it only needs sizes of members and load conditions. The method was applied on 2D frame – shear wall structure with 10 floors, 15 floors, 20 floors, and 30 floors to test the sensitivity of this method on complex structures. Plastic hinge is located on both ends of members and modeled as rotational springs which will represent the inelastic behavior of the structure and its elements. The shear wall was idealized to an equivalent frame which its behavior will represent the shear wall behavior. The subsequent design by using the secant stiffness method shows that this method can accurately estimate the inelastic strength and ductility demand of an earthquake resistant structure only by using a linear approach on complex structures.